The Coffee Crisis, Early Childhood Development, and Conditional Cash Transfers - Seth R. Gitter; James Manley; Bradford Barham (Inter-American Development Bank (IDB), 2011)
This paper examines the efficacy of three conditional cash transfer (CCT) programs in Honduras, Mexico, and Nicaragua in mitigating the potential negative effects of an income shock caused by falling prices of coffee, an important cash crop to many CCT participants. A theoretical household model is developed that demonstrates both the positive potential of CCTs to mitigate negative shocks effects on early childhood development and the negative potential of CCTs to exacerbate the impacts of a negative shock to early childhood development if the conditionality encourages households to shift resources from younger to older children to sustain their school attendance. The experimental design includes both CCT and non-CCT households and communities with and without coffee production. The paper finds that in Mexico the CCT mitigated the negative shock on child height-for-age z-scores, while in Nicaragua coffeeproducing households who participated in CCTs saw greater declines in z-scores. Findings for Honduras are largely inconclusive.
Keywords: H43; I12; I38; O15; 330